PENGARUH FAKTOR TAM TERHADAP REPURCHASE INTENTION (Studi Kasus Dompet Digital Go-Pay) - timotius sutrisno (FEB Universitas Sam Ratulangi Manado, 2023)
The Covid-19 pandemic has had an impact on changing patterns of activity in society. Previously, various activities could be carried out freely, now apart from having to comply with health protocols, there are also mobility restrictions. Of course, this is one of the drivers of digitization in almost all sectors. No exception, the payment system. This study aims to see the effect of security, ease of use, and privacy concern on repurchase intention mediated by a trust to Go- Pay e-wallet users in Surabaya. The population in this study is the millennial generation, Go- Pay digital wallet users in Surabaya, with a sample of 385 respondents. This study uses data collection through an online survey via a google form. This non-probability sampling technique uses the purposive sampling method. The results of this study indicate that security, ease of use, and privacy significantly influence repurchase intentions mediated by trust in Go-Pay digital wallet users in the city of Surabaya. The results of this study can be used as a theoretical basis to increase the repurchase intention of e-wallets by creating trust in users, increasing the security of e-wallet applications, and the ease of use of e-wallets, and expanding the protection of data privacy of Go-Pay e-wallet users.